Microbiology : An introduction - Tortora, Gerard J.; Funke, Berdell R.; Case, Christine L., 1948- (San Francisco, Calif. ; London : Pearson Benjamin Cummings, 2007)
Reflecting the constantly evolving field of microbiology and its research environment, this ninth edition provides the most up-to-date coverage of technology and applications using straightforward presentation of complex topics.
Previous ed.: 2003.
Includes index.
CD-ROM in front pocket.
Keywords: Microbiology; Science